Enactive explorations of children's sensory-motor play and therapeutic handling in physical therapy - Håkstad, Ragnhild B.; Øberg, Gunn Kristin; Girolami, Gay L.; Dusing, Stacey C. (Frontiers in Rehabilitation Sciences, 2022)
Introduction: In pediatric physical therapy there is an ongoing debate about the use of therapeutic handling and its potential effects on motor learning. In this study, we build on enactive theoretical perspectives to explore the role of therapeutic handling in connection to children’s sensory-motor play, engagement, and performance during a single physical therapy session. Material and methods: This is a qualitative study based on video-observations of therapy sessions and interviews with 15 physical therapists (PTs) each treating two different children aged 0-3. The authors utilized a framework of co-reviewing, discussing, and reflecting on the sessions. Themes were identified and used to describe the ways by which PTs’ therapeutic handling unfolds, with connections to theories on sensory-motor play and learning, along with enactive perspectives on embodiment, experience, mutual incorporation and sense-of-agency. Results: The characteristics and purposes of therapeutic handling are presented in two main themes: 1) Position and support, and 2) Directing movement. We found that position and support promoted sensory-motor improvement when the PTs’ handling aligned with the child’s play interests and engagements. As part of play, the children used new and additional support surfaces to self-initiate better posture and movement solutions and reach play goals. The PTs’ ways of directing movements varied. To awaken curiosity and induce a child’s self-driven motor exploration the PT needs to be subtle, flexible, and precise in the directing of movement. This entails responsiveness to the child’s signals and a bodily know-how in the placing of hands and direction of pressure to enable the child to actively participate in and eventually self-drive movement. Discussion: Therapeutic handling that is mutually incorporated between PT and child can enrich the child’s playing-to-learn-to-move process by providing novelty and facilitating the child’s sense-of-agency in the self-initiated exploration and refinement of movement possibilities. In the PTs’ effort to merge therapeutic handling with children’s play, the momentum of interaction can open new therapeutic windows of movement experience and learning opportunities.